TIGAR inhibits ischemia/reperfusion-induced inflammatory response of astrocytes. (15th March 2018) - Chen, Jieyu; Zhang, Ding-Mei; Feng, Xing; Wang, Jian; Qin, Yuan-Yuan; Zhang, Tian; Huang, Qiao; Sheng, Rui; Chen, Zhong; Li, Mei; Qin, Zheng-Hong
Abstract: The inflammatory response of glial cells contributes to neuronal damage or repair after brain ischemia/reperfusion insult. We previously demonstrated a protective role of TP53-induced glycolysis and apoptosis regulator (TIGAR) in ischemic neuronal injury through increasing the flow of pentose phosphate pathway (PPP). The present study investigated the possible role of TIGAR in ischemia/reperfusion-induced inflammatory response of astrocytes. Male ICR mice were subjected to middle cerebral artery occlusion for 2 h followed by 24 h reperfusion and cultured primary astrocytes were subjected to oxygen glucose deprivation for 9 h followed by 24 h reoxygenation (OGD/R). Adenoviral vectors were used to alter the levels of TIGAR protein in brain and in culture primary astrocytes. We showed that during the OGD/R insult the protein levels of TIGAR were rapidly increased in astrocytes. Overexpression of TIGAR mediated increased the viability, levels of NADPH and rGSH, and reduced intracellular reactive oxygen species (ROS) in cultured primary astrocytes. Overexpression of TIGAR not only significantly reduced infarct volume after stroke insult but also markedly reduced long-term mortality and improved recovery of neurological functions. Overexpression of TIGAR tempered OGD/R- or ischemia/reperfusion-induced the upregulation of inducible nitric oxide synthase (iNOS), cyclooxygenases COX2 and the release of pro-inflammatory cytokines interleukin 1 beta (IL-1β) and tumor necrosis factor-α (TNF-α), while TIGAR knockdown produced opposite effects on these parameters. Moreover, Overexpression of TIGAR suppressed OGD/R-induced degradation of IκBα and NF-κB nuclear translocation in cultured primary astrocytes. The present study elucidates a novel mechanism by which TIGAR protects neurons against ischemia/reperfusion injury. Highlights: TIGAR was rapidly upregulated in astrocytes in response to ischemic insult. TIGAR played a positive role in survival of astrocytes after stroke attack. TIGAR inhibited ischemia-induced activation of NF-κB in astrocytes, presumably by reducing ROS. TIGAR inhibited astrocyte-mediated inflammatory response after I/R through increasing PPP flux.